Aesthetics and Functions of Praise Poetry: A Case Study of a Dagara Tradition - Poghyaar-Kuutiero, J. (University Of Ghana, 1997)
DanU is a popular art form among the Dagara. It is literally a praise song or chant performed to celebrate the exploits of an individual in the community. Its characteristics conveniently locate it within the realm of poetry despite its orality. Its poetic features which include figurative expressions, such as metaphors, similes and hyperboles generally elevate its language above the normal speech level. Formal and prosodic features like structural repetitiveness, parallelism and alliteration infuse it with rhythm that underscores its belongingness to poetry. As praise poetry, danu is dynamic and grows with time as events of the past are neatly interwoven with those of the present. It is one oral art form that has a long range and extends into other verbal art forms like the dirge and the grinding song. DanU is popular not only because of "its aesthetic value , but also because of its sociological and psychological functions among the people. For that reason the artists of this genre are accorded reverence in terms of the relevance of their creative compositions and performances .
MPhil. English
Keywords: Poetry; Dagara Tradition; DanU